Can Scintimammography Help Differentiate the Nature of Suspected Masses Identified in Breast Ultrasound among Young Patients? - Gharepapagh, Esmaeil; Akhoundi, Neda; Fakhari, Ashraf; Seifi, Batool; Sedghian, Sonia; Ranjkesh, Mahnaz; Sarfaraz, Tohid; Siami, Alireza; Nia, Iman Yazdani (World Journal of Nuclear Medicine, 2025)
Breast cancer is the second leading cause of cancer deaths among women. Given the limitations of mammography in detecting breast cancer among young patients with suspected masses identified through ultrasound, our study aims to assess the effectiveness of scintimammography in distinguishing the nature of these masses.The study included 123 patients between the ages of 18 and 35, who were presented with breast masses categorized as Breast Imaging-Reporting and Data System III and IV based on ultrasound findings. A total of 134 breast masses were identified in the patients through ultrasound examination. Patients underwent radiopharmaceutical injection of 99mTc-MIBI (technetium-99m methoxyisobutylisonitrile) with a 15 to 20 mCi dose. The radiopharmaceutical uptake in the scans was assessed using a scoring system ranging from 0 to 3. Then, the scores were compared with biopsy results.There was a statistically significant relationship between the absorption score reported by scintimammography and the pathological findings (p = 0.001). The sensitivity and specificity of scintimammography in malignant masses considering cutoff point of 2 for absorption score were 96 and 92%, respectively.Based on the obtained results, scintimammography could be considered a diagnostic and complementary method to ultrasound in evaluating benign and malignant breast masses in young patients with dense breasts.
Keywords: scintimammography; ultrasound; biopsy